2017
DOI: 10.1111/ocr.12184
|View full text |Cite
|
Sign up to set email alerts
|

Centre‐level variation in outcomes and treatment for otitis media with effusion and hearing loss and the association of hearing loss with developmental outcomes at ages 5 and 7 years in children with non‐syndromic unilateral cleft lip and palate: The Cleft Care UK study. Part 2

Abstract: Structured AbstractObjectives: To explore centre-level variation in otitis media with effusion (OME), hearing loss and treatments in children in Cleft Care UK (CCUK) and to examine the association between OME, hearing loss and developmental outcomes at 5 and 7 years.Setting and Sample Population: Two hundred and sixty-eight 5-year-old British children with non-syndromic unilateral cleft lip and palate (UCLP) recruited to CCUK. Materials and Methods:Children had air and bone conduction audiometry at age 5.Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 39 publications
2
37
2
Order By: Relevance
“…In this supplement, we have explored centre‐level variability across a range of treatment and outcome measures. Our results, which are reported in full in each respective paper in this supplement, suggest that there was centre‐level variation in several of these treatment indicators and outcomes across the domains of oral health, audiology and speech . Describing and exploring these centre‐level variations is important for several reasons.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this supplement, we have explored centre‐level variability across a range of treatment and outcome measures. Our results, which are reported in full in each respective paper in this supplement, suggest that there was centre‐level variation in several of these treatment indicators and outcomes across the domains of oral health, audiology and speech . Describing and exploring these centre‐level variations is important for several reasons.…”
Section: Discussionmentioning
confidence: 67%
“…We have described a standard hierarchical statistical model to predict centre‐level means and centre‐level variation and highlighted how to interpret the output from these models using the expository examples of facial growth and appearance. We found modest differences between centres in the age at assessment and gender of the children over and above that which may be expected from sampling variation and so we controlled for these differences in the analysis presented in this paper and in the subsequent papers in this supplement . We found no evidence of centre‐level variation in dento‐alveolar relationships and facial appearance.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Long-term hearing loss due to improper treatment for OME can negatively influence language development of children [45]. Hearing loss in children suffering from CLP can also affect their academic comprehension and learning performance [38,[45][46][47]. Bess et al reported that academic performance can be seriously affected in up to 33% of children including those suffering hearing loss in only one ear.…”
Section: Consequences Of Ome In Clpmentioning
confidence: 99%
“…28 Hearing loss in children suffering from cleft palate can also affect their academic comprehension and learning performance. [28][29][30] Bess et al reported that academic performance can be seriously affected in up to a third of children including those suffering hearing loss in only one ear. They also reported that up to 40% of patients are unable to participate in regular activities or interactions due to hearing loss.…”
Section: Discussionmentioning
confidence: 99%